ENTERPRISE RISK MANAGEMENT, PERFORMANCE MEASUREMENT SYSTEMS AND ORGANIZATIONAL PERFORMANCE IN MALAYSIAN PUBLIC LISTED FIRMS - Abdul Rasid, Siti Zaleha; Golshan, Nargess; Mokhber, Mozhdeh; Tan, Gi-Gi; Mohd-Zamil, Nor Aiza (International Journal of Business and Society, 2017)
There has been a call for integrating a strategic performance measurement system and enterprise risk management (ERM) as a proposed best practice for risk management. This study examines the effects of ERM and performance measurement systems (PMS) on organizational performance. In addition, this study also examines the effects of a linked ERM-PMS tool on organizational performance. The research method involved administering an online questionnaire survey to 196 public listed firms. The respondents were the head of risk management department of the firms. In the case of ERM and PMS effects on organizational performance, the result of simple linear regression supported the research hypotheses. However the results from the moderated multiple regression which was employed to test the joint effect of ERM and PMS on organizational performance did not support the research hypothesis. Based on the study results it is recommended that firms may practice ERM and PMS separately rather than linking them together, since their integration may complicate the PMS framework. Keywords: Enterprise Risk Management; Performance Measurement System; Balanced Scorecard; Organizational Performance.